Multisource Assessment in Conjunction with Emotional Intelligence Can Be Used for Monitoring the Development of Residents’ Professional Competencies - YEGEN, BERRAK; SARIKAYA, ÖZLEM (Springer, 2017)
The aim of the study is to assess the professional competencies and to examine the relations of those skills with emotional intelligence dimensions during the post-graduate medical education of the residents. The study was conducted on residents studying at medical and surgical departments of a university hospital. The data were gathered with multisource (self, peer, trainer, and nurse) feedback forms regarding 64 medical residents in 12 departments. In addition, Emotional Quotient Inventory (EQ-i) was implemented to each of the residents. While the trainer-, peer-, and nurse-assessment results of the professional skills of the residents were correlated with each other, no correlation was present between the self-assessments and the scores of external assessors. Moreover, positive and negative relationships were found among the EQ-i domains and some items of professional competencies of the residents. In conclusion, use of multisource feedback forms in evaluating professional competencies of residencies has shown reliable results among external raters. Using these forms together with EQ-i can provide some opportunities for monitoring the development of professional skills in post-graduate medical education. © 2017, International Association of Medical Science Educators.
Keywords: Emotional intelligence; Multisource assessment; Postgraduate medical education; Professional skills assessment; Residency education